2010
DOI: 10.1158/1078-0432.ccr-10-0318
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label, Phase I Study of the Polo-like Kinase-1 Inhibitor, BI 2536, in Patients with Advanced Solid Tumors

Abstract: Purpose: This phase I, open-label, dose-escalation study investigated the maximum tolerated dose (MTD) of BI 2536, a small-molecule polo-like kinase (Plk)-1 inhibitor, in two treatment schedules in patients with advanced solid tumors. Secondary objectives included evaluation of safety, efficacy, and pharmacokinetics.Experimental Design: Patients received a single i.v. dose of BI 2536 as a 1-hour infusion on days 1 and 8 or a single 24-hour infusion on day 1 of each 21-day treatment course. MTD determination wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 16 publications
5
62
1
1
Order By: Relevance
“…In parallel with the present study, BI 2536 was also investigated in another phase i repeated dose-escalation study in patients with advanced solid tumours 20 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In parallel with the present study, BI 2536 was also investigated in another phase i repeated dose-escalation study in patients with advanced solid tumours 20 .…”
Section: Discussionmentioning
confidence: 92%
“…In that study, patients received intravenous infusions of BI 2536 on days 1 and 8 of a 3-week treatment course 20 . The mtd for the latter dosing schedule was defined as 200 mg (100 mg on day 1 and 100 mg on day 8).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that BI-2536 has potent tumoricidal activity against cancer cells, particularly those harboring mutations in TP53 (44-47). BI-2536 was the subject of several clinical trials in patients with cancers of the lung, breast, ovaries, and uterus (48)(49)(50)(51)(52)(53). Although it showed evidence of efficacy in cancer patients, its development was abandoned after phase II trials revealed unacceptable toxicity (grade 4 neutropenia) at subtherapeutic doses.…”
Section: Chemically Modified β-Cyclodextrins Can Encapsulate Small Hymentioning
confidence: 99%
“…Volasertib has shown in vivo efficacy in multiple xenograft models, including AML. A predecessor compound, BI 2536, 15,16 was previously evaluated in older patients with relapsed/refractory AML and provided a first proof-of-principle of the potential therapeutic value of targeting Plk in patients with AML. 17 Clinical development of BI 2536 was discontinued in favor of volasertib, which has an improved pharmacokinetic profile.…”
Section: Introductionmentioning
confidence: 99%